2019
DOI: 10.1017/dmp.2019.95
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study on Risk Perceptions and Knowledge of Fentanyl Exposure Among New York State First Responders

Abstract: Objectives:The present opioid epidemic and abuse of fentanyl in the United States has led to an increased risk of exposure to first responders. Law enforcement, fire, and emergency medical services are receiving misinformation on fentanyl health and safety risks and this has led to miscommunication. Understanding the risk perceptions and knowledge of first responders regarding fentanyl can help identify training gaps.Methods:A 15-item 6-point Likert scale online questionnaire was developed and distributed to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…In the Persaud/Jennings 2019 survey of New York State law enforcement officers, firefighters, and EMS personnel (discussed above), 37% of EMS/firefighters and 24% of law enforcement officers answered that hand sanitizer is safe to use after handling fentanyl. 34 If alcohol-based hand sanitizer increases transdermal absorption, then the approximately one-third of first responders who believe hand sanitizer is safe to use may be at increased risk of harm. No other studies examining knowledge or utilization of decontamination methods were identified.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the Persaud/Jennings 2019 survey of New York State law enforcement officers, firefighters, and EMS personnel (discussed above), 37% of EMS/firefighters and 24% of law enforcement officers answered that hand sanitizer is safe to use after handling fentanyl. 34 If alcohol-based hand sanitizer increases transdermal absorption, then the approximately one-third of first responders who believe hand sanitizer is safe to use may be at increased risk of harm. No other studies examining knowledge or utilization of decontamination methods were identified.…”
Section: Resultsmentioning
confidence: 99%
“…[31][32][33] The second study was a 2019 survey of 187 New York state law enforcement officers, firefighters, and emergency medical technicians regarding knowledge of fentanyl exposure and PPE. 34 The study found that responders generally agreed with expert risk perceptions of fentanyl but had lower agreement with expert recommendations on PPE. Most respondents understood the need to protect their eyes, nose, and mouth when working with fentanyl and to not disturb fentanyl without PPE.…”
Section: Personal Protective Equipmentmentioning
confidence: 87%
See 2 more Smart Citations
“…Despite a consistent stream of media accounts of overdose from fentanyl exposure, few studies have reported on officer perceptions of this misinformation. A survey of first responders in New York found that 80% believed "briefly touching fentanyl could be deadly" (Persaud & Jennings, 2020). To our knowledge, only one study has reported on the effects of correcting this perception.…”
Section: Introductionmentioning
confidence: 98%